An investigation of coronaphobia and physical activity among patients with rheumatoid arthritis - Gonca Sağlam; Emine Esra Ergül (Archives of Rheumatology, 2022)
Objectives: This study aims to investigate coronaphobia and physical activity levels in patients with rheumatoid arthritis (RA). Patients and methods: Between December 2021 and February 2022, a total of 68 RA patients (11 males, 57 females; mean age: 48.3±10.1 years; range, 29 to 78 years) and 64 age- and sex-matched healthy individuals (4 males, 60 females; mean age: 47.9±10.2 years; range, 23 to 70 years) were included in this cross-sectional study. Demographic, physical, lifestyle, and medical characteristics of all participants were recorded. The COVID-19 Phobia Scale (C19PS) and the International Physical Activity Questionnaire-Short Form (IPAQ-SF) were administered to all participants. The RA patients were divided into two groups as: patients treated with biological and non-biological agents. The Disease Activity Score-28 (DAS28) and Clinical Disease Activity Index (CDAI) were used to measure disease activity. Results: The total and subgroup scores of the C19P-S were found to be statistically significantly higher in both the biological and non-biological RA groups than in the control group (p=0.001). However, there was no statistically significant difference between the RA groups in terms of total and subgroup C19P-S scores. The mean IPAQ score was significantly lower in the RA group using biological drugs than in the control group (p=0.002). A significant correlation was found between DAS28 and total C19P-S scores (r:0.63, p<0.05), and CDAI and total C19P-S scores (r:0.79, p<0.05). Conclusion: Patients with RA have an increased risk of coronaphobia and disease activity is correlated with coronaphobia. Patients treated with biological agents seem to have lower activity levels compared to other RA patients and healthy controls. These results should be considered in the management of RA during COVID-19 pandemic and preventive intervention strategies should be formulated to cope with coronaphobia.